2020
DOI: 10.1002/pro.3791
|View full text |Cite
|
Sign up to set email alerts
|

Current developments in Coot for macromolecular model building of Electron Cryo‐microscopy and Crystallographic Data

Abstract: Coot is a tool widely used for model building, refinement, and validation of macromolecular structures. It has been extensively used for crystallography and, more recently, improvements have been introduced to aid in cryo‐EM model building and refinement, as cryo‐EM structures with resolution ranging 2.5–4 A are now routinely available. Model building into these maps can be time‐consuming and requires experience in both biochemistry and building into low‐resolution maps. To simplify and expedite the model buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
499
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 597 publications
(500 citation statements)
references
References 49 publications
(91 reference statements)
0
499
0
1
Order By: Relevance
“…Based on symmetry considerations, we also concluded that ZP-C(I) and EGF IV/ZP-N(I) belong to two distinct additional copies of UMOD (chains B and C, respectively; corresponding to UMOD 2 and UMOD 4 in Figure 2), both of which interact with chain A as well as with each other. The resulting initial set of coordinates, consisting of one chain encompassing the whole polymerization region of UMOD (A) and two half chains (B, C), was subjected to molecular dynamics (MD) flexible fitting in Namdinator (Kidmose et al, 2019) and manually rebuilt using Coot (Casañal et al, 2019) as implemented in CCP-EM (Burnley et al, 2017) . After further improvement by Cryo_fit (Kim et al, 2019b) , as well as additional rebuilding in Coot (whose carbohydrate-building tool (Emsley and Crispin, 2018) was used to add the N-glycan chains attached to EGF IV N322, ZP-N N396 and ZP-C N513) and ISOLDE (Croll, 2018) , the model was real-space refined against the UMOD fl data in PHENIX (Afonine et al, 2018a) using a data/restraint weight of 0.8, a non-bonded weight of 250.0 and restraints generated using the starting coordinates as a reference.…”
Section: Model Building Refinement Validation and Analysismentioning
confidence: 99%
“…Based on symmetry considerations, we also concluded that ZP-C(I) and EGF IV/ZP-N(I) belong to two distinct additional copies of UMOD (chains B and C, respectively; corresponding to UMOD 2 and UMOD 4 in Figure 2), both of which interact with chain A as well as with each other. The resulting initial set of coordinates, consisting of one chain encompassing the whole polymerization region of UMOD (A) and two half chains (B, C), was subjected to molecular dynamics (MD) flexible fitting in Namdinator (Kidmose et al, 2019) and manually rebuilt using Coot (Casañal et al, 2019) as implemented in CCP-EM (Burnley et al, 2017) . After further improvement by Cryo_fit (Kim et al, 2019b) , as well as additional rebuilding in Coot (whose carbohydrate-building tool (Emsley and Crispin, 2018) was used to add the N-glycan chains attached to EGF IV N322, ZP-N N396 and ZP-C N513) and ISOLDE (Croll, 2018) , the model was real-space refined against the UMOD fl data in PHENIX (Afonine et al, 2018a) using a data/restraint weight of 0.8, a non-bonded weight of 250.0 and restraints generated using the starting coordinates as a reference.…”
Section: Model Building Refinement Validation and Analysismentioning
confidence: 99%
“…Protein and rRNA chains were visually inspected in Coot (Casañal et al, 2020) and manually adjusted where residues did not fit well into the density. Focused-refined maps on smaller regions were used to make further manual adjustments to the model, alternating with PHENIX RSR.…”
Section: Modelingmentioning
confidence: 99%
“…Recent developments (Frenz et al, 2017; Igaev et al, 2019) in molecular dynamics programs have provided methods for fitting atomic models to electron density maps using methods independent of classical crystallographic programs such as COOT (Casanal et al, 2019; Emsley and Cowtan, 2004) or PHENIX (Adams et al, 2010), which have themselves added cryo-EM optimised functions, and which would appear to work well for “mid-to-low” resolution cryo-EM maps which have previously been difficult to interpret with the crystallographic packages. We have not used these here, although are investigating their use for other protein complexes.…”
Section: Discussionmentioning
confidence: 99%